Microwave-assisted multicomponent reaction in water leading to highly regioselective formation of benzo[f]azulen-1-ones - Wang, Shu-Liang (2011)
Microwave-assisted three-component reaction has been established for the regioselective synthesis of benzo[f]azulen-1-ones. The reaction was performed in aqueous media under microwave irradiation by using readily available and inexpensive starting materials. A total of 38 examples were examined to show a broad substrate scope and good overall yields (70–89%). The present new synthesis shows attractive green chemistry characteristics, such as the use of water as reaction media, concise one-pot conditions, short reaction periods (7–24 min), easy work-up/purification and reduced waste production without the use of any strong acids or metal promoters.